2010
DOI: 10.1021/ja906648w
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Highly Regioselective Aminotrifluoroacetoxylation of Alkenes

Abstract: We report a highly regioselective metal-free oxidative cyclization of sulfonamides onto tethered, unactivated alkenes using hypervalent iodine and Brønsted acids. Under these conditions the acid counterion is incorporated into the cyclized products providing an overall aminotrifluoroacetoxylation of the alkene. An unusual preference for endo ring closure is exhibited in contrast to existing exo selective methods. Multiple ring sizes can be formed to access functionalized pyrrolidines, piperidines, and azepanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(82 citation statements)
references
References 15 publications
8
72
0
2
Order By: Relevance
“…By contrast, the two-component heteroarylation of olefins bearing tethered O-or N-nucleophiles did not proceed to afford the expected tetrahydrofurans or pyrrolidines: in the case of 4-penten-1-ol, a complex mixture of products was obtained, whilst N-(4-pentenyl)tosylamide furnished a 9:1 mixture of piperidine 15 and pyrrolidine 16 (Scheme 2, bottom). Although the essential role of gold in related aminooxygenations has been demonstrated under basic conditions, [32] we found that, as expected under acidic conditions, [33] the formation of 15 and 16 proceeded equally efficiently in the absence of gold. [25] In all cases, the oxyarylation products were accompanied by alkyl 2-iodobenzoates, formed in situ from the IBA-de- …”
Section: Scope-monosubstituted Olefinssupporting
confidence: 60%
“…By contrast, the two-component heteroarylation of olefins bearing tethered O-or N-nucleophiles did not proceed to afford the expected tetrahydrofurans or pyrrolidines: in the case of 4-penten-1-ol, a complex mixture of products was obtained, whilst N-(4-pentenyl)tosylamide furnished a 9:1 mixture of piperidine 15 and pyrrolidine 16 (Scheme 2, bottom). Although the essential role of gold in related aminooxygenations has been demonstrated under basic conditions, [32] we found that, as expected under acidic conditions, [33] the formation of 15 and 16 proceeded equally efficiently in the absence of gold. [25] In all cases, the oxyarylation products were accompanied by alkyl 2-iodobenzoates, formed in situ from the IBA-de- …”
Section: Scope-monosubstituted Olefinssupporting
confidence: 60%
“…[64] While the degree of diastereo-and regioselectivity are substrate dependent, this reaction is notable as it reports the first example of the direct oxyamination of homoallylic amines to exhibit both 6-endo and anti selectivity regarding addition across the alkene geometry, see 99 a to 100 a.…”
Section: Metal-free Oxidation Protocolsmentioning
confidence: 99%
“…This unusual endo selectivity was exploited in the concise, stereoselective synthesis of (À)-pseudoconhydrine. [64] Iodine(V) reagents: Iodine(V) has also been used to effect the direct oxyamination of olefins by Nicolaou et al [65] In this procedure, the exposure of N-arylamides 101 to DessMartin periodinane (DMP) delivered iso-imidoquinone intermediates 102, which underwent [4 + 2] Diels-Alder reactions with a range of electron-rich alkenes to afford the desired 2-amilides 103 (Scheme 43). [66] This methodology was applied in the core synthesis of various complex natural products such as elisabethin A and pseudopterosin A (Figure 3).…”
Section: Metal-free Oxidation Protocolsmentioning
confidence: 99%
“…One possible reason for this is the lack of suitable carbon electrophiles that can activate the carbon-carbon double bond of the allylic amide. [14,15] To the best of our knowledge, there are no examples of such a catalytic electrophilic carbofunctionalization of this class of molecules. Despite these advances, the development of novel methods that catalytically generate carbon electrophiles capable of activating alkenes to nucleophilic attack remains a challenge; the solution to this challenge would be of significant use in complex molecule synthesis.…”
mentioning
confidence: 99%